If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 + -5x = 12 + -7x Solving 60 + -5x = 12 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 60 + -5x + 7x = 12 + -7x + 7x Combine like terms: -5x + 7x = 2x 60 + 2x = 12 + -7x + 7x Combine like terms: -7x + 7x = 0 60 + 2x = 12 + 0 60 + 2x = 12 Add '-60' to each side of the equation. 60 + -60 + 2x = 12 + -60 Combine like terms: 60 + -60 = 0 0 + 2x = 12 + -60 2x = 12 + -60 Combine like terms: 12 + -60 = -48 2x = -48 Divide each side by '2'. x = -24 Simplifying x = -24
| 0.05s+.1(6000-s)=375 | | 2(4x-2)-5x=-18 | | n-5*10=80 | | -29-10(15)=-18(15)+91 | | 5(2x+1)+4(3x-2)= | | 324*5x*y=4x | | 0.05+600-s=375 | | -2p+7=3x-(5p+1) | | 25=7m+4 | | -9+w=-32 | | 42.72=.99+27x | | -29-10n=-18n+91 | | 2=3(x-5)+1-2x | | 3b+17=29 | | 5(2x-7)+42-3x=2 | | 17k=5k-2 | | 10(-10)=0 | | 3x-x+10-12=-188 | | 42.72=.99+x | | 0.4(-0.04-7x)=-2.7x | | 12x-6x=36 | | 5z+2=17 | | -29-10n=-18n+9 | | a=x | | -4n+3=13 | | 14x+23=4x+173 | | 11-2x+8x+5=32 | | r+1/3=8/3 | | (x^2-2x)-180=0 | | 9=g+3 | | -(12-4x)+8(10-4x)= | | 34=t+15 |